Brak bezpośredniego wpływu umiejętności percepcyjnych na umiejętności narracyjne dzieci z niedokształceniem mowy pochodzenia korowego - Balcerzak, Renata Balcerzak (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
In the paper, an analysis of information gathered during examinations of children with speech development disorder of cortical origin is presented. The study group consisted of 4 individuals (two girls and two boys), aged 5–10. The results of the examination of phonemic awareness and understanding of a few sentences-long spoken texts as well as articulating a few sentences-long texts suggested a possible correlation between these two types of skills (phonemic awareness, spoken text understanding and production). However, a thorough analysis of the results does not allow one to conclude that the specific phonemic awareness deficits and/or speech perception difficulties have a predominant influence on the narrative skills of children with speech development disorder of cortical origin. Although the main hypothesis was disproved, the results of the analysis shed light on another possible explanation of speech production difficulties in the abovementioned speech and language disorder: deficient/insufficient auditory attention and/or verbal working memory. Such explanation has not yet been taken into consideration in the research on speech and language development disorder of cortical origin.